The Validity of the Okun’s Law in the Turkish Economy: A Comparative Analysis on General Unemployment and Non-Agricultural Unemployment Rate - Bayramoğlu, Arzu; Aybudak, Huri Gül (Fırat Üniversitesi, 2023)
In macroeconomic theory, the relationship between unemployment and economic growth is examined by Okun's Law. According to this law, the negative relationship between economic growth and unemployment rate is known as the coefficient of the Okun. In the unemployment debate, different unemployment rates are important as well as the general unemployment rate. Non-agricultural unemployment rate is one of them. In the study, two different models and two Okun coefficients were obtained to analyze the relationship between the general unemployment rate and the non-agricultural unemployment rate and economic growth, in the Turkish economy in the period of 2005Q1- 2019Q2 by using ARDL cointegration method. According to the econometric findings obtained, Okun's Law is valid in the Turkish economy in the period examined. Thus, when the economic growth rate is 1% above the average growth rate of the relevant period 5.3%, the general unemployment rate decreases by 0.07%, while the non-agricultural unemployment rate decreases by 0.08%. This result shows that there is a stronger relationship between non-agricultural unemployment and economic growth rate than the general unemployment rate.

Makro iktisat teorisinde işsizlik ile ekonomik büyüme arasındaki ilişki Okun Yasası ile incelenmektedir. Bu yasaya göre ekonomik büyüme ile işsizlik oranı arasındaki ilişkiyi belirleyen negatif yönlü katsayı okun katsayısı olarak bilinmektedir. Günümüzde işsizlik tartışmalarında genel işsizlik oranının yanı sıra farklı işsizlik oranları öne çıkmaktadır. Tarım dışı işsizlik oranı bunlardan biridir. Bu bağlamda bu çalışmada Türkiye ekonomisinde 2005Q1- 2019Q2 döneminde Okun Yasası’nın geçerliliği genel işsizlik oranı ve tarım dışı işsizlik oranları üzerinden karşılaştırmalı olarak analiz edilmektedir. Çalışmada ekonomik büyüme ile işsizlik oranı arasındaki ilişki ARDL eşbütünleşme yöntemi ile incelenmektedir. Çalışmada genel işsizlik oranı ve tarım dışı işsizlik oranının ekonomik büyüme ile olan ilişkisini analiz etmek için iki ayrı model kurulmuş ve iki ayrı Okun katsayısı elde edilmiştir. Elde edilen ekonometrik bulgulara göre incelenen dönemde Türkiye ekonomisinde Okun Yasası geçerlidir. Buna göre ekonomik büyüme oranı ilgili dönem ortalama büyüme oranı olan %5,3’ün % 1 üzerine çıktığında genel işsizlik oranı % 0,07 azalırken, tarım dışı işsizlik oranı % 0,08 azalmaktadır. Bu sonuç tarım dışı işsizlik ile ekonomik büyüme oranı arasında genel işsizlik oranına göre daha güçlü bir ilişki olduğunu göstermektedir.
TÜRKİYE EKONOMİSİNDE OKUN YASASI’NIN GEÇERLİLİĞİ: GENEL İŞSİZLİK VE TARIM DIŞI İŞSİZLİK ORANI ÜZERİNDEN KARŞILAŞTIRMALI BİR ANALİZ